Social Forestry and the Food–Energy–Water Nexus: Strengthening Local Sovereignty to Support Asta Cita 2 Priorities - Khulfi M. Khalwani; Bambang Kustiawan; Apik Karyana (CV. AFDIFAL MAJU BERKAH, 2026)
Asta Cita 2, as articulated in Presidential Regulation No. 12 of 2025 on the National Medium-Term Development Plan (RPJMN) 2025–2029, emphasizes the strengthening of defense resilience and the achievement of resource sovereignty in the food–water–energy sectors as core pillars of Indonesia’s national security agenda. Within this policy framework, this study examines the future prospects of Indonesia’s Social Forestry program as a strategic instrument to support these objectives. Using a systematic literature review (PRISMA) combined with policy analysis, the paper explores how community-based forest management contributes to ecological stability, economic diversification, and local empowerment. The findings indicate that Social Forestry enhances socio-economic resilience through livelihood expansion, strengthens landscape security by reducing land degradation, and supports non-military defense strategies through increased community capacities. These contributions are further reinforced by the alignment of Social Forestry with national development priorities under the RPJMN 2025–2029, particularly in promoting village-based economic transformation, green economy pathways, and non-military defense resilience. Despite this enabling regulatory environment, governance challenges persist, including limited institutional support, uneven market access, and regulatory inconsistencies. Nevertheless, Social Forestry holds substantial potential as a national strategic instrument for realizing Asta Cita 2 through the integration of forest-based enterprises, sustainable economic models, and village-level resilience initiatives. The paper concludes by proposing policy innovations to strengthen regulatory coherence and maximize the contribution of Social Forestry to Indonesia’s national security and resource sovereignty objectives.